Astrophysical entomology: dissecting the black widow population through multi-band light curve modelling. Issue Volume 16:Issue S363(2020) (June 2020) - Mata Sánchez, Daniel; Kennedy, Mark R.; Clark, Colin J.; Breton, Rene P.; Dhillon, Vikhram S.
Abstract: The population of black widows, binary systems containing a millisecond pulsar and a very low-mass companion star exposed to the high-energy pulsar wind, has grown exponentially in the past few years. The number of black widow candidates is now over 30 systems, but only 14 have been confirmed so far. Their relevance in analysing the extremes of the neutron stars properties led to multiwavelength dedicated studies that revealed a rich phenomenology. In this work, we provide a glimpse into the black widow class through modelling of high-cadence multi-band light curves of 6 systems, accounting for almost half of the confirmed population. A better understanding of the black widow population, which hosts some of the most massive and fastest spinning neutron stars, will ultimately benefit future modelling of compact object mergers.